CHEMICAL CHARACTERISTICS OF FERMENTED COW’S MILK IN LIGHT GREEN COCONUT FARM (Cocos nucifera L. var. varidis Hassk) - L., JUITA; LINDAWATI, S. A.; MIWADA, I N. S. (Majalah Ilmiah Peternakan; Vol 25 No 2 (2022): Vol. 25 No. 2 (2022), 2022)
The purpose of this research was to determine the chemical characteristics of fermented cow’s milk kefir in light green coconut shells (Cocos nucifera L. var. viridis Hassk). The research was conducted from August to Oc- tober 2020 at the Laboratory of Animal Products Technology, Faculty of Animal Science, Udayana University. The experimental design used in the study was a completely randomized design (CRD) with three treatments and five replications. The three treatments were fermented cow’s milk in a jar as a control (P0), and fermented cow’s milk in a light green coconut shell (Cocos nucifera L. var. viridis Hassk) without coconut meat (P1), cow’s milk fermented in light green coconut shell (Cocos nucifera L. var. viridis Hassk) with coconut meat (P2). The variables observed in the research were total acid, lactose content, fat content, and protein content. The research data were analyzed using variance, if the effect of the treatment was significantly different (P<0.05), it was followed by Duncan’s mul- tiple range test. The results showed that the total acid in P2 and P1 treatments were significantly (P<0.05) higher by 36.05% and 29.07% than the P0 treatment, but between P2 and P1 treatments were not significantly different (P>0,05). Lactose content, fat content, and protein content in all treatments (P2, P1 and P0) showed no significant differences (P>0.05). The conclusion of this study that fermented cow’s milk kefir in light green coconut shells (Co- cos nucifera L. var. Viridis Hassk) has an effect on total acid but does not affect lactose content, fat content, and protein content.